Low-Noise Amplifier for Deep-Brain Stimulation (DBS) - Nordi, Tiago Matheus; Gounella, Rodrigo Henrique; Luppe, Maximiliam; Junior, João Navarro Soares; Fonoff, Erich Talamoni; Colombari, Eduardo [UNESP]; Romero, Murilo Araujo; Do Carmo, João Paulo Pereira (MDPI, 2022)
Deep-brain stimulation (DBS) is an emerging research topic aiming to improve the quality of life of patients with brain diseases, and a great deal of effort has been focused on the development of implantable devices. This paper presents a low-noise amplifier (LNA) for the acquisition of biopotentials on DBS. This electronic module was designed in a low-voltage/low-power CMOS process, targeting implantable applications. The measurement results showed a gain of 38.6 dB and a −3 dB bandwidth of 2.3 kHz. The measurements also showed a power consumption of 2.8 µW. Simulations showed an input-referred noise of 6.2 µVRMS . The LNA occupies a microdevice area of 122 µm × 283 µm, supporting its application in implanted systems.
Keywords: CMOS; Deep-brain stimulation (DBS); Implantable devices; Low-noise amplifier